Comparison of the effects and complications of unilateral spinal anesthesia versus standard spinal anesthesia in lower-limb orthopedic surgery - Tekye,Seyyed Mostafa Moosavi (2014)
Introduction: A restricted sympathetic block during spinal anesthesia may minimize hemodynamic changes. This prospective randomized study compared unilateral and bilateral spinal anesthesia with respect to the intra- and postoperative advantages and complications of each technique. Material and methods: Spinal anesthesia was induced with 0.5% hyperbaric bupivacaine and a 25-G Quincke needle (Dr. J) in two groups of patients with physical status ASA I-II who had been admitted for orthopedic surgeries. In group A, dural puncture was performed with the patient in a seated position using 2.5 cm3 of hyperbaric bupivacaine. Each patient was then placed in the supine position. In group B, dural puncture was performed with the patient in the lateral decubitus position with 1.5 cm3 of hyperbaric bupivacaine. The lower limb was the target limb. The speed of injection was 1 mL/30 s, and the duration of time spent in the lateral decubitus position was 20 min. Results: The demographic data were similar in both groups. The time to the onset of the sensory and motor block was significantly shorter in group A (p = 0.00). The duration of motor and sensory block was shorter in group B (p < 0.05). The success rate for unilateral spinal anesthesia in group B was 94.45%. In two patients, the spinal block spread to the non-dependent side. The incidence of complications (nausea, headache, and hypotension) was lower in group B (p = 0.02). Conclusion: When unilateral spinal anesthesia was performed using a low-dose, low-volume and low-flow injection technique, it provides adequate sensory-motor block and helps to achieve stable hemodynamic parameters during orthopedic surgery on a lower limb. Patients were more satisfied with this technique as opposed to the conventional approach. Furthermore, this technique avoids unnecessary paralysis on the non-operated side.